A new species of Chiasmocleis Méhely, 1904 (Anura: Microhylidae) from the Peruvian Amazonia - Rojas-Padilla, Omar; Gagliardi-Urrutia, Giussepe; Rios-Alva, Ehiko J.; Castroviejo-Fisher, Santiago (Zootaxa, 2022)
We describe a new species of Chiasmocleis from the Amazonian forest of Peru. The new species is characterized by its medium size (snout-to-vent length = 18.2–20.8 mm in females, and 16.5 mm in one male), hands and feet with slightly developed fridges in females (more developed in male), and presence of a femoral line in all individuals. We also infer its phylogenetic position using DNA sequences of fragments of the mitochondrial genes for 16S rRNA and cytochrome oxidase subunit 1 (COI), and describe the mineralized skeleton through 3D models generated by computed tomography (CT-scan). Based on our results, we discuss the variation of some osteological characters traditionally used in the systematics of the genus.